A Novel Polyvalent Bacteriophage vB_EcoM_swi3 Infects Pathogenic Escherichia coli and Salmonella enteritidis - Sui, Bingrui; Han, Lili; Ren, Huiying; Liu, Wenhua; Zhang, Can (Frontiers in Microbiology, 2021)
A novel virulent bacteriophage vB_EcoM_swi3 (swi3), isolated from swine feces, lyzed 9% (6/65) of Escherichia coli and isolates 54% (39/72) of Salmonella enteritidis isolates, which were all clinically pathogenic multidrug-resistant strains. Morphological observation showed that phage swi3 belonged to the Myoviridae family with an icosahedral head (80 nm in diameter) and a contractile sheathed tail (120 nm in length). At the optimal multiplicity of infection of 1, the one-step growth analysis of swi3 showed a 25-min latent period with a burst size of 25-plaque-forming units (PFU)/infected cell. Phage swi3 remained stable both at pH 6.0–8.0 and at less than 50°C for at least 1 h. Genomic sequencing and bioinformatics analysis based on genomic sequences and the terminase large subunit showed that phage swi3 was a novel member that was most closely related to Salmonella phages and belonged to the Rosemountvirus genus. Phage swi3 harbored a 52-kb double-stranded DNA genome with 46.02% GC content. Seventy-two potential open reading frames were identified and annotated, only 15 of which had been assigned to functional genes. No gene associated with pathogenicity and virulence was identified. The effects of phage swi3 in treating pathologic E. coli infections in vivo were evaluated using a mouse model. The administration of a single intraperitoneal injection of swi3 (106 PFU) at 2 h after challenge with the E. coli strain (serotype K88) (108 colony-forming units) sufficiently protected all mice without toxic side effects. This finding highlighted that phage swi3 might be used as an effective antibacterial agent to prevent E. coli and S. enteritidis infection.